2001
DOI: 10.1002/1532-2890(2000)52:1<62::aid-asi1061>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The use of theory in information science research

Abstract: We report on our findings regarding authors' use of theory in 1,160 articles that appeared in six information science (IS) journals from 1993-1998. Our findings indicate that theory was discussed in 34.1% of the articles (0.93 theory incidents per article; 2.73 incidents per article when considering only those articles employing theory). The majority of these theories were from the social sciences (45.4%), followed by IS (29.9%), the sciences (19.3%), and humanities (5.4%). New IS theories were proposed by 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 4 publications
0
32
1
1
Order By: Relevance
“…A summary of selected examples of studies in LIS between 1991 and 2005 (White & Marsh, 2006) included the use of CA to identify reasons for selecting initial web search strategies (White & Iivonen, 2001), to develop a thesaurus of image-text relationships (Marsh & White, 2003), and to determine the nature of problem statements in LIS articles (Stansbury, 2002). Similarly, Pettigrew and McKechnie (2001) used a CA codebook of three categories (e.g., Affiliation of First Author, Primary Subject of Article, and Type of Article) to analyze the use of theory in 1,160 articles that appeared in six information science (IS) journals between 1993 and 1998.…”
Section: Content Analysismentioning
confidence: 99%
“…A summary of selected examples of studies in LIS between 1991 and 2005 (White & Marsh, 2006) included the use of CA to identify reasons for selecting initial web search strategies (White & Iivonen, 2001), to develop a thesaurus of image-text relationships (Marsh & White, 2003), and to determine the nature of problem statements in LIS articles (Stansbury, 2002). Similarly, Pettigrew and McKechnie (2001) used a CA codebook of three categories (e.g., Affiliation of First Author, Primary Subject of Article, and Type of Article) to analyze the use of theory in 1,160 articles that appeared in six information science (IS) journals between 1993 and 1998.…”
Section: Content Analysismentioning
confidence: 99%
“…However, social theory has a somewhat larger presence in the conceptualizations underlying studies of societallevel impacts of computing (e.g., Nardi & O'Day, 1999). Additionally, Pettigrew and McKechnie (2001) found that more than 45 percent of the library and information science literature cites social theories. However, many of the studies in this literature do not explicitly focus on the roles of ICTs and thus are not considered social informatics work.…”
Section: Empirical and Theory-based Focusmentioning
confidence: 99%
“…According to two recent reviews of the information systems and library and information science literatures, there is only a small number of social theorists whose works are used in studies of ICTs (see Jones, 2000;Pettigrew & McKechnie, 2001). There are two additional approaches that, while not appearing in either Pettigrew and McKechnie's or Jones's literature reviews, serve as important theoretical underpinnings for social informatics research.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…Therefore, to achieve a holistic understanding of a user's information behavior, LIS research must extend the discussion to take in not only a user's physical behaviors but also a user's state of knowing. Understanding humans' states of knowing has been traditionally discussed in the philosophical community, and many scholars have proposed different philosophical approaches based on positivism, pragmatism, and phenomenology to help establish better epistemological tools to understand the phenomena of information behavior in the LIS research (Budd, 1995(Budd, , 2005Hjørland, 2005aHjørland, , 2005bPettigrew & McKechnie, 2001;Sundin & Johannisson, 2005). In an extensive introduction to pragmatism and neo-pragmatism, Sundin and Johannisson (2005, p. 24) suggested that knowledge is "enacted though linguistic and physical actions whose significances and relevance are judged by the consequences of such actions."…”
Section: The Epistemological Concern and Philosophical Pragmatism In mentioning
confidence: 99%
“…To provide a better system or service to accommodate people's need for information, information behavior research faces the complex challenge of bringing two traditional trends together: providing not only the physical access to material objects but also access to the ideas that a user needs in different situations in order to meet the purpose of increasing a user's knowledge in a certain domain. To meet this challenge, many scholars have proposed different approaches based on positivism, pragmatism, and phenomenology in LIS research (Budd, 1995(Budd, , 2005Hjørland, 2005aHjørland, , 2005bPettigrew & McKechnie, 2001;Sundin & Johannisson, 2005). Information behavior in LIS research can be seen as influenced by the concerns of epistemology because obtaining useful knowledge is the main purpose of an information seeking activity (e.g.…”
Section: Introductionmentioning
confidence: 99%